Identifikasi Potensi Pengembangan Dan Kelayakan Usaha Komoditi Buah-Buahan Unggulan Agribisnis Di Kota Binjai - Sanjaya, Budi; Ginting, Rahmanta; Effendi, Ihsan (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
The production of superior, important and prospective horticultural products in Binjai City during the period 2010-2015 shows a fluctuating pattern. This happened not only in the vegetable commodity, but also in the fruit commodity group. The purpose of this study is to analyze the potential of superior fruit commodities in agribusiness and analyze the level of business feasibility of developing superior commodity commodities in agribusiness in the City of Binjai. Data uses primary and secondary data. The analysis tools used are Location Quotient (production value) and farm feasibility analysis (Revenue Cost ratio). The results showed that the fruit commodities which became the basic agricultural commodities in most districts in the City of Binjai were rambutan, mango, papaya, banana, guava, and breadfruit. Soursop commodity is a base fruit commodity in 4 sub-districts. Avocado, duku / langsat, guava, mango, pineapple, papaya, banana, rambutan and sapodilla commodity are fruit commodities in 3 districts. Star fruit, durian, guava, tangerine, jackfruit, snake fruit, breadfruit and yam bean commodities became commodity base fruits in 2 sub-districts. Value of Return Cost Ratio (RCR) obtained from rambutan farming is 29.10; water guava (honey guava) is 2.05 and yam is 3.63 per arable area / year. It can be concluded that rambutan, guava and yam farming are efficient and feasible to be cultivated.